FREQUENCY OF NON-DIABETIC RENAL DISEASE IN TYPE 2 DIABETES MELLITUS PATIENTS UNDERGOING RENAL BIOPSY - Khan, Muhammad Zeeshan; Hussain, Mudassar; Khan, Azhar; Hassan, Usman; Akhter, Noreen; Hameed, Maryium; Mushtaq, Sajid; Awan, Usman (Journal of Ayub Medical College Abbottabad, 2021)
Background: Diabetes mellitus has become a major emerging health concern. Its burden, estimated to be 451 million in 2017, has been projected to rise to 693 million by 2045. This will bring a rise in the prevalence of its associated complications. There is a wide spectrum of non-diabetic renal disease (NDRD) known to be present in diabetic patients with variable prevalence. However, the majority of diabetes mellitus (DM) patients with renal disease are yet not biopsied and the diagnosis of diabetic nephropathy (DN) is presumed on clinical grounds. Methods: It is a retrospective cross-sectional study. We selected a total of 126 cases of renal biopsies with a history of type 2 diabetes mellitus. Demographic data was collected from the medical records and pathology reports while all cases were evaluated by reviewing the archived slides. Results: Patients were categorized into group 1 with isolated NDRD, group 2 showing NDRD mixed with DN and group 3 with isolated DN. Thirty-four (27%) cases had isolated NDRD (group 1), 14 (11%) had NDRD mixed with DN and 78 (62%) patients had isolated DN. NDRD, either alone or in combination with DN, was found to be present in 48 patients with an overall prevalence of 38%. Conclusion: Our study concludes that NDRD is frequent in type 2 diabetes mellitus patients. Renal biopsy remains the key diagnostic tool in such cases, providing crucial information for proper management of the underlying pathology.